Aquatic macrophytes as feeding site for small fishes in the Rosana Reservoir, Paranapanema River, southeastern Brazil - Casatti, L. [UNESP]; Mendes, H. F.; Ferreira, K. M. (FapUNIFESP (SciELO), 2003)
In the present investigation we studied the feeding habits of the fishes associated with aquatic macrophytes in the Rosana Reservoir, southeastern Brazil. Twenty fish species were collected during four field trips, regularly distributed across the dry and wet seasons. Focal snorkeling observations of the fishes were made over a total of six hours. Nine species were present in abundances of more than 1% and, therefore, had their feeding habits analyzed. Hemigrammus marginatus, Roeboides paranensis, Hyphessobrycon eques, Astyanax altiparanae, Serrasalmus spilopleura, and Bryconamericus stramineus were predominantly invertivores, with predominance of aquatic insects (Diptera, Ephemeroptera, and Trichoptera immatures) among their food items. The predominantly algivores were Apareiodon affinis, Serrapinnus notomelas, and Satanoperca pappaterra, with high frequency of filamentous blue-green algae, diatoms, clorophyts, and periderm. The different microhabitat exploitation plus diet composition suggests partitioning of resources and absence of food competition among the most representative fish species in the studied community, indicating the importance of the naturalistic approach to fish ecology studies.

Neste trabalho foram estudados os hábitos alimentares dos peixes associados a bancos de macrófitas aquáticas no reservatório de Rosana, Sudeste do Brasil. Vinte espécies de peixes foram coletadas em quatro viagens, regularmente distribuídas em períodos de seca e chuva. Seis horas de observações subaquáticas pelo método animal focal foram realizadas. Nove espécies apresentaram abundâncias relativas maiores do que 1% e tiveram seus hábitos alimentares investigados. Hemigrammus marginatus, Roeboides paranensis, Hyphessobrycon eques, Astyanax altiparanae, Serrasalmus spilopleura e Bryconamericus stramineus foram predominantemente invertívoros, com predominância de insetos aquáticos (imaturos de Diptera, Ephemeroptera e Trichoptera). Os predominantemente algívoros foram Apareiodon affinis, Serrapinnus notomelas e Satanoperca pappaterra, com elevada ocorrência de algas cianofíceas filamentosas, diatomáceas, clorofíceas e periderme. A diferenciada exploração de microhabitats, em combinação com a dieta propriamente dita, sugere partilha dos recursos alimentares e ausência de competição por alimento entre as espécies mais representativas na comunidade de peixes estudada, ressaltando a importância de abordagens naturalísticas em estudos sobre ecologia de peixes.
Macrófitas aquáticas como sítio de alimentação para pequenos peixes no reservatório de Rosana, rio Paranapanema, Sudeste do Brasil
Keywords: Aquatic macrophytes; Fishes; Feeding; Rosana reservoir; Paranapanema river; Macrófitas aquáticas; Peixes; Alimentação; Reservatório de Rosana; Rio Paranapanema